2019
DOI: 10.1083/jcb.201903018
|View full text |Cite
|
Sign up to set email alerts
|

Disease-associated mutations in Niemann-Pick type C1 alter ER calcium signaling and neuronal plasticity

Abstract: Tiscione et al. report a molecular mechanism that links lysosomal cholesterol export with the regulation of key intracellular Ca2+ signaling pathways to influence synaptic architecture in health and neurodegenerative NPC1 disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
54
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 65 publications
3
54
1
Order By: Relevance
“…Two studies in NPC1 neurons obtained controversial results: while Xu et al (2010) reported no differences in spine density [63], Tiscione et al (2019) observed that NPC1 deficiency results in a decrease in neuronal spine density [106]. Thus, based on the published data, it appears that alterations of synaptic spines do not follow the same trend among all neurological LSD.…”
Section: Defects In Synaptic Spinesmentioning
confidence: 99%
“…Two studies in NPC1 neurons obtained controversial results: while Xu et al (2010) reported no differences in spine density [63], Tiscione et al (2019) observed that NPC1 deficiency results in a decrease in neuronal spine density [106]. Thus, based on the published data, it appears that alterations of synaptic spines do not follow the same trend among all neurological LSD.…”
Section: Defects In Synaptic Spinesmentioning
confidence: 99%
“…In the study by Tiscione et al (4), several key conclusions can be made. First, the loss of function of the NPC1 cholesterol transporter results in increased flux of Ca 2+ at the plasma membrane, yet decreased ER Ca 2+ levels and overall increased resting cytosolic Ca 2+ in NPC patient fibroblasts with different disease-causing mutations in the NPC1 gene as well as in NPC1 null cells and a pharmacologically induced NPC cell model.…”
mentioning
confidence: 98%
“…Going back to the cholesterol defect in NPC, the study explores the role of the classical cholesterol biosynthesis and regulation pathways, namely, the membrane-bound sterol regulatory element binding protein (SREBP) pathway. From their data, the authors conclude that activation of SREBP contributes to the Ca 2+ imbalance and signaling protein defects observed in NPC (4).…”
mentioning
confidence: 99%
See 2 more Smart Citations